Chinese FDI in New Zealand: What Are Chinese Investors Looking For?. (22nd September 2016) - Ge, Gloria L.; Stringer, Christina; Ding, Daniel Z.
Abstract : In recent years, there has been unparalleled growth in outward foreign direct investment from China. Traditional Western‐dominated international business theory proposes that asset exploitation is necessary for firms undertaking foreign investment. However, more recently, studies suggest asset augmentation is more important for multinational enterprises from emerging countries. This article examines the acquisition by two Chinese firms—Agria and Haier—of two iconic New Zealand firms, each with a significant international presence—PGG Wrightson and Fisher & Paykel. The article determines that Agria and Haier invested to acquire strategic assets in order to strengthen their position in the Chinese market as well as build and sustain a global position. Strategic intent was an important factor in deciding where to invest, and strategic assets complementary to their own competitive advantages were sought by the Chinese firms. © 2016 Wiley Periodicals, Inc .